Structural Properties of G,T-Parallel Duplexes - Aviñó, Anna; Cubero, Elena; Gargallo, Raimundo; González, Carlos; Orozco, Modesto; Eritja, Ramon (Journal of Nucleic Acids, 2010)
The structure of G,T-parallel-stranded duplexes of DNA carrying similar amounts of adenine and guanine residues is studied by means of molecular dynamics (MD) simulations and UV- and CD spectroscopies. In addition the impact of the substitution of adenine by 8-aminoadenine and guanine by 8-aminoguanine is analyzed. The presence of 8-aminoadenine and 8-aminoguanine stabilizes the parallel duplex structure. Binding of these oligonucleotides to their target polypyrimidine sequences to form the corresponding G,T-parallel triplex was not observed. Instead, when unmodified parallel-stranded duplexes were mixed with their polypyrimidine target, an interstrand Watson-Crick duplex was formed. As predicted by theoretical calculations parallel-stranded duplexes carrying 8-aminopurines did not bind to their target. The preference for the parallel-duplex over the Watson-Crick antiparallel duplex is attributed to the strong stabilization of the parallel duplex produced by the 8-aminopurines. Theoretical studies show that the isomorphism of the triads is crucial for the stability of the parallel triplex.